2017
DOI: 10.1002/bit.26303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant density on recombinant hemagglutinin yields in an Agrobacterium‐mediated transient gene expression system using Nicotiana benthamiana plants

Abstract: Agrobacterium-mediated transient expression systems enable plants to rapidly produce a wide range of recombinant proteins. To achieve economically feasible upstream production and downstream processing, it is beneficial to obtain high levels of two yield-related quantities of upstream production: recombinant protein content per fresh mass of harvested biomass (g gFM ) and recombinant protein productivity per unit area-time (g m /month). Here, we report that the density of Nicotiana benthamiana plants during up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…This suggests that the average PPFD, rather than the PPFD during a particular period e.g., for a few days before gene transfer , affected the accumulation level of HA in leaves. These results for leaf HA content per unit FM are consistent with results from our recent study in which leaf HA content per unit FM was significantly lowered when plant density was high 400 plants m 2 , Fujiuchi et al, 2017 , as dense planting decreases the amount of light received by a plant. In contrast, Shang et al 2018 reported that supplemental lighting with LEDs and dense planting in a greenhouse before gene transfer had little or no effect on leaf HA content per unit of biomass.…”
Section: Effects Of Ppfdsupporting
confidence: 91%
“…This suggests that the average PPFD, rather than the PPFD during a particular period e.g., for a few days before gene transfer , affected the accumulation level of HA in leaves. These results for leaf HA content per unit FM are consistent with results from our recent study in which leaf HA content per unit FM was significantly lowered when plant density was high 400 plants m 2 , Fujiuchi et al, 2017 , as dense planting decreases the amount of light received by a plant. In contrast, Shang et al 2018 reported that supplemental lighting with LEDs and dense planting in a greenhouse before gene transfer had little or no effect on leaf HA content per unit of biomass.…”
Section: Effects Of Ppfdsupporting
confidence: 91%
“…Changing environmental conditions at appropriate times during each stage may be required to obtain a high yield [56]; a high-nitrate nutrient solution during the pre-inoculation state results in high recombinant protein content [55]. Very recently, interest in the surrounding environment has extended beyond research into the plant itself [57,58,71]. Nitrate-enriched fertilizers that enable plant growth [55], immediate desiccation after agro-infiltration [56], and slightly lower plant density [57], are critical factors for improving plant biomass.…”
Section: Transient Expression Systemsmentioning
confidence: 99%
“…Very recently, interest in the surrounding environment has extended beyond research into the plant itself [57,58,71]. Nitrate-enriched fertilizers that enable plant growth [55], immediate desiccation after agro-infiltration [56], and slightly lower plant density [57], are critical factors for improving plant biomass. Plant density, the number of plants per unit growth area, and the effect of leaf position affect harvested biomass, and are therefore, important factors for achieving economically feasible production [57].…”
Section: Transient Expression Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have described the expression of a viral proton channel to stabilize labile proteins in the cell secretory pathway (Jutras et al., 2015, 2018), the expression of a human convertase to promote the post-translational proteolytic processing of clinically useful proteins in vivo (Wilbers et al., 2016; Mamedov et al., 2019), or the exogenous induction of the jasmonic acid defense pathway to reduce endogenous protein content in leaf tissue prior to recombinant protein purification (Robert et al., 2015). In parallel, studies have documented the effects of cultural practices on N. benthamiana growth and leaf biomass production before agroinfiltration (Fujiuchi et al., 2014; Shang et al., 2018), the influence of environmental parameters in growth chambers following agroinfiltration (Matsuda et al., 2017, 2018), or the impact of plant density on overall protein yield in specific culture settings (Fujiuchi et al., 2017; Shang et al., 2018).…”
Section: Introductionmentioning
confidence: 99%